2018
DOI: 10.1111/bjep.12220
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of teacher emotions on their approaches to teaching: A structural equation modelling approach

Abstract: Identifying this pattern of relationships will contribute to understanding the reasons why new teaching strategies are often not adopted despite well-designed professional programs and educational reform and will provide implications for teaching improvement through teacher emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 57 publications
5
72
2
13
Order By: Relevance
“…Literature recognises emotions as a significant factor that contributes to the teaching experience and impacts educators' beliefs, judgements and motivation (Chen, 2018;Schutz et al, 2006). However, empirical research on the emotional perspectives of teaching in higher education continues to be scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature recognises emotions as a significant factor that contributes to the teaching experience and impacts educators' beliefs, judgements and motivation (Chen, 2018;Schutz et al, 2006). However, empirical research on the emotional perspectives of teaching in higher education continues to be scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the theory of planned behavior affirms (Ajzen, 2005), the attitudes of individuals constitute the best predictor of their behavior. In this sense, one of the aspects that most frequently seems to positively affect inclusive education (IE) in the classroom is related to the attitudes and beliefs of teachers, whether they are professionally in-service teachers (de Boer et al, 2011;Chen, 2018;Glock et al, 2018) or future teachers (Sharma et al, 2014). In addition, attitudes are not innate but learned (Ajzen, 2005).…”
Section: Attitudes Toward Inclusive Educationmentioning
confidence: 99%
“…Classrooms and schools are flooded with emotions which highlights the significance of teacher emotions (Hargreaves, 2005;Day and Gu, 2013). Existing research has found that teacher emotions influence not only their instructional choices (Chen, 2019), well-being (Burić et al, 2019), and effectiveness (Huang et al, 2019b) but also their students' emotions (Frenzel et al, 2018), the teacher -student relationship , and learning outcomes (Burić, 2019). Given that teaching is full of emotions, how teachers manage their emotions becomes an important matter of interest.…”
Section: Introductionmentioning
confidence: 99%